The Effects of Khula during Death Illness: A Comparative Legal and Jurisprudential Study - Rehab Moustafa Kamel Alsayed (International Journal of Law Research and Studies, 2024)
This research deals with the hypothesis of the occurrence of Khul’ in the death illness of one of the spouses, and since it is most likely permissible for a foreigner to donate to pay the compensation for Khul’ to the husband instead of his wife, the research also deals with the hypothesis that Khul’ occurs in the death illness of this foreigner who donated to pay the compensation. In the research, I conducted a comparative study between Islamic jurisprudence and personal status laws, where I addressed the position of each of them regarding the problems of the research. In this research, I have adopted the inductive approach, relying on the Holy Quran, the books of the Noble Prophetic Sunnah, the books of Islamic jurisprudence, as well as personal status laws. Through it, I have concluded that divorce in the event of a terminal illness is valid according to Sharia, whether the husband is the terminally ill patient, or the wife, or even a stranger who guarantees the compensation for divorce. As for the amount of compensation, jurists have differed on it according to whether the wife is the patient, the husband, or the stranger. As for personal status laws, most of them have been silent about all the hypotheses of the issue, relying on referring to a doctrine that is referred to when the law is devoid of a specific issue, or relying on the existence of a text that addresses the actions of the terminally ill patient in general, whether by the same law or civil law.
Keywords: Khula; Death Illness; Islamic Jurisprudence; Personal Status Laws; Comparative Study